A Method for Beam Positions Determination in Image Reconstruction - Rena Widita (Indonesian Journal of Physics, 2006)
From one treatment to the next, considerable effort is made to accurately position the patient consistent with the plan, but some variation is unavoidable. The target volume and the organ at risks may move within the patient and/or change shape during the treatment. Thus, it is important to be able to verify the success of the treatment by determining the position of patient and the dose deposited in the patient at each fraction. One possibility to achieve this would be to obtain an image while the patient is on the treatment couch. The aim of this study was to develop a method for determining beam positions to use to reconstruct an image for dose verification by collecting limited information while the patient is on the treatment couch. Two methods, image correlation and projection correlation, were developed and compared here. The effectiveness and practicality of each of these methods were compared. The results show that the projection correlation presents several advantages. It can be applied without any iterations, and it produces a fast algorithm. With more advanced image reconstruction software, this method could potentially be used in a clinical environment.